A nominalização como estratégia discursiva em crônicas jornalísticas - Martinelli, Ivan Neves (2023)
This dissertation's theme is nominalization as a project of saying in journalistic chronicles, with the general objective of analyzing how the strategy of nominalization as an argumentative resource contributes to the construction of the project of saying in journalistic chronicles with an environmental theme, published in electronic magazines. The work has the following specific objectives: to highlight how nominalization contributes to textuality and textual sequencing; demonstrate how nominalization favors or does not favor the development of the text's argumentative proposal and describe how nominalization strategies are used to express the author's approach or distance from the topic and demonstrate whether the nominalization strategy contributes to the project of saying in a text narrative. This is applied research, in terms of nature; from the point of view of its objectives, it is classified as exploratory; and regarding procedures, it is bibliographic with a qualitative approach. The theoretical assumption is the studies on the topic undertaken by work in the area of ​​Textual Linguistics. To this end, the principles and concepts of Textual Linguistics and their contribution to understanding the nominalization strategy as a resource that is increasingly being used for textual, discursive and referential progression were taken into account. Four chronicles were analyzed and we can say that the results allow us to say that the nominalization strategy is really efficient in the process of constructing the project of saying'.